2001
DOI: 10.5194/angeo-19-723-2001
|View full text |Cite
|
Sign up to set email alerts
|

Geomagnetic control of the spectrum of traveling ionospheric disturbances based on data from a global GPS network

Abstract: Abstract.In this paper an attempt is made to verify the hypothesis of the role of geomagnetic disturbances as a factor in determining the intensity of traveling ionospheric disturbances (TIDs). To improve the statistical validity of the data, we have used the method involving a global spatial averaging of disturbance spectra of the total electron content (TEC). To characterize the TID intensity quantitatively, we suggest that a new global index of the degree of disturbance should be used, which is equal to the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
41
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 36 publications
6
41
0
1
Order By: Relevance
“…These results are in reasonably good agreement with data reported by Afraimovich et al ( , 2001bAfraimovich et al ( , 2001cAfraimovich et al ( , 2002aAfraimovich et al ( , 2002b. Phase measurements are more sensitive to equipment failures and to various interference affecting the GPS ''satellite-receiver'' channel when compared with group delay measurements that are directly used for navigation purposes.…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…These results are in reasonably good agreement with data reported by Afraimovich et al ( , 2001bAfraimovich et al ( , 2001cAfraimovich et al ( , 2002aAfraimovich et al ( , 2002b. Phase measurements are more sensitive to equipment failures and to various interference affecting the GPS ''satellite-receiver'' channel when compared with group delay measurements that are directly used for navigation purposes.…”
Section: Discussionsupporting
confidence: 95%
“…The high positive correlation between the growth of the density of phase slips and the intensity of ionospheric irregularities during geomagnetic disturbances as detected by Afraimovich et al ( , 2001aAfraimovich et al ( , 2001bAfraimovich et al ( , 2002aAfraimovich et al ( , 2002b, points to the fact that the increase in slips is caused by the scattering of the GPS signal from ionospheric irregularities. Afraimovich et al (2001c) found that the growth of The same as in Fig. 9, but for the magnetically disturbed day of July 15, 2000 (day 197) Fig.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…4N, 88.1E), and the monitoring system of ionosphere disturbances according to the GPS signals receivers data (Afraimovich et al, 2001). Irkutsk ISR is located in 98 km to the north-west of Irkutsk.…”
Section: Methodsmentioning
confidence: 99%
“…Notice that waveguide modes have been studied before [Francis, 1973a, b], and the results are being widely used for theoretical works and for interpreting observation of various disturbances, including those in the upper atmosphere [Shibata, Okuzawa, 1983;Afraimovich et al, 2001;Vadas, Liu, 2009;Vadas, Nicolls, 2012;Idrus et al, 2013;Heale et al, 2014;Hedlin, Drob, 2014 et al]. Francis [Francis, 1973a, b] defined dispersion characteristics and vertical structures of waveguide modes.…”
Section: Introductionmentioning
confidence: 99%